ApbZIP2-mediated enhancement of lipid productivity supports sustainable plant-based omega-3 biomanufacturing - Rong Zhou; Kairui Mu; Ya’nan Shi; Yuqin Li; Liwen Luo; Yunkai Tan; Zhenyao Wang; Yufang Tang; Xuan Li (Bioresource Technology, 2027)

Microplastic pollution and ecological risks in the wet season: Potential effects on bacterial communities and nitrogen cycling in a coastal watershed of Southeast China - Yaling Huang; Suofang Zhong; Wantao Lin; Shoufeng Zhang; Hua Jiang; Xuan Wang; Jingli Mu (Marine Pollution Bulletin, 2026)

Extraction optimization, purification, and structural characterization of Yacon polysaccharide: An inhibitor against α-glucosidase/α-amylase - Zhen-Zhou Li; Zhe-Xuan Mu; Shao-Feng Li; Yi-Han Ding; Shadrack Vundi Benjamin; Ruo-Jia Zhu; Xiang-Yu Wang; Zhen-Yu Wang; Hua Zhang (Food Chemistry, 2026)

Hydraulic response and failure mechanism of red-bed mudstone slope under cycling freeze–thaw conditions: a comparison study - Xuan Mu; Longqi Li (Transportation Geotechnics, 2026)

Sustainable high internal phase emulsions based on millet bran nanocellulose and EGCG: Centrifugal fabrication, antioxidant reinforcement, and 3D printability - Mo Chen; Yu-hao Wu; Xu Guo; Jin-yue Sun; Nan Chen; Mu-xuan Wang; Qi-dong Ren; Mohamed A. Farag; Nilufar Z. Mamadalieva; Min Wang; Meng-qi Zhang; Chao Liu (Food Chemistry, 2026)

Effects of slab folding on magma production in the Sumatra subduction zone - Yongliang Bai; Jiahao Tian; Yuanpeng Liu; Dongdong Dong; Shiguo Wu; Sanzhong Li; Xuan Mu (Earth and Planetary Science Letters, 2026)

Aging-Related Changes in the Injury Response of the Peripheral Nervous System - Yue-Yan Cen; Mu-Yun Wang; Qin-Xuan Song; Xin-Lin Gao; Cheng Zhou; Chun-Jie Li; Fei Liu; Yan-Yan Zhang; Jie-Fei Shen (Neuroscience Bulletin, 2026)
Peripheral nerve injury (PNI) significantly impairs patients’ quality of life, with elderly individuals experiencing particularly severe consequences due to aging-related declines in neuronal injury response and repair capabilities. Processes of the generation and transmission of injury signals, axonal disruption, initiation of regeneration, and the elongation of regenerating axons, as well as the subsequent reinnervation by these axons, are all significantly influenced by aging. These alterations are closely associated with changes in mitochondrial function, neuronal transport systems, a persistent inflammatory milieu, and various microenvironmental non-neuronal cells. Therefore, this review synthesized the pivotal role of aging in the multifaceted regulation of the nervous system following PNI and highlighted promising molecular regulatory mechanisms in the signaling pathways. Furthermore, it identified critical areas for future research, including unresolved questions in age-associated injury responses, potential targets for pharmacological intervention, and emerging therapeutic strategies meriting consideration for research and development.

Mitochondrial Communication Networks in the Bone Microenvironment: From the Maintenance of Homeostasis to Translational Interventions for Bone Diseases - Wentao Wang; Kun Wang; Wenjing Wang; Xuan Mu; Zhiquan Cheng; Guangzhi Zhang; Xuewen Kang; Yonggang Wang (Stem Cell Reviews and Reports, 2026)

A Hybrid 1D U-Net and Fuzzy Inference Method for Rapid Prediction of Residual Ultimate Bending Moment Ratio of Damaged Ship Hull Girders - Xuan Li; Jinlei Mu; Yuan Zhang; Yuchen Hu; Fuyu Yan (Journal of Marine Science and Engineering, 2026)
The residual ratio of ultimate bending moment is a critical indicator for hull structural safety assessment of damaged ships. In maritime emergency scenarios, the empirical formula method has insufficient prediction accuracy, while nonlinear finite element (FE) simulation bears prohibitive computational cost. To address this limitation, we propose a rapid surrogate model for predicting the residual ultimate bending moment ratio of side-damaged ships. The model integrates a lightweight one-dimensional U-Net (1D U-Net) for nonlinear feature extraction and multi-scale feature fusion and a fuzzy inference module for embedding engineering prior constraints. Trained on a 1D structured dataset generated via the modified Smith method (covering multiple damage conditions, hogging and sagging), the model achieves an overall mean absolute error (MAE) of 1.79% and root mean squared error (RMSE) of 2.39% on the test set. It outperforms empirical formulas in accuracy with ultra-short inference time, far lower computational cost than FE simulation, and provides engineering interpretability via activated fuzzy rules. This work offers an efficient alternative tool for rapid safety assessment of damaged hull structures.

Two undescribed benzofuran derivatives from chaetomium elatum - Chen-Yi Yan; Feng Ju; Yu-Hui Chen; Yu-Ting Mu; Yun-Jie Hu; Da-Le Guo; Yun Deng; Qi-Xuan Kuang (Natural Product Research, 2026)

Tailoring nitric oxide-release hydrogel incorporating MSC-derived exosomes for multimodal therapy of diabetic foot ulcers - Kaijie Zhao; Xuan Tian; Qijian Wei; Yuteng Li; Mingzhuo Zhou; Anhui Mu; Xin Yan; Shilei Ni; Pei Liu (Chemical Engineering Journal, 2026)

Mining allergens in Cryptotympana atrata nymphs: integrating proteomics and homology-based bioinformatics - Yuan He; Shu-tao Sun; Jian-bo Xiao; Qi-dong Ren; Ying-ying Chen; Meng-qi Zhang; Mu-xuan Wang; Xu Guo; Jin-yue Sun; Chao Liu (Food Chemistry, 2026)

Polystyrene microplastics at environmentally realistic concentrations exacerbate diatom blooms caused by phosphorus pollution: Rethinking coastal eutrophication - Xuan Hou; Muhammad Waseem; Muhammad Waseem Boota; Li Mu; Yuanyuan Wei; Xiangang Hu (Water Research, 2026)

A non-destructive Ammonia-based pork freshness detection method utilizing UV-DOAS and spectral reconstruction fitting neural network - Yufei Ju; Rui Zhu; Mu Li; Xuan Wang; Xijun Wu; Yungang Zhang (Food Chemistry, 2026)

Effects of taurine on immunity and ammonia metabolism in large-scale loach under ammonia stress - Ruo-Yu Zhou; Lu Chen; Meng-Yang Hu; Mu-Xi Li; Yu-Xuan Fei; Mei Huang; Yun-Long Zhang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Effects of farmland shelterbelts on water erosion at regional scale: a case study in the black soil region of Northeast China - Suhua Zhu; Xuan Mu; Xiao Zheng; Xingyi Li; Lining Song (Agroforestry Systems, 2026)

Beyond astaxanthin: The bioactive ingredients of Haematococcus pluvialis and their applications in food - Shu-tao Sun; Yan-jie Jiang; Jesus Simal-Gandara; Xu Guo; Shengxiang Yang; Ying-ying Chen; Meng-qi Zhang; Qi-dong Ren; Mu-xuan Wang; Jin-yue Sun; Ning-yang Li; Chao Liu (Trends in Food Science & Technology, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Discovery of novel nuciferine-based URAT1 inhibitors for hyperuricemia: synthesis, biological evaluation, and computational insights - Yan-fei Liu; Ze-sheng Hao; Xu Guo; Shu-tao Sun; Mu-xuan Wang; Meng-qi Zhang; Ying-ying Chen; Jin-yue Sun; Chao Liu (Medicinal Chemistry Research, 2026)

Simultaneous removal of nitrate and ammonia at the sulfur/pyrite-microbe interface: A novel insight of pyrite in wastewater polishing treatment for nitrogen metabolism - Jianjun Luo; Cheng Hou; Zijun Wang; Ningyuan Gui; Yi-Xuan Wang; Xinbai Jiang; Yang Mu; Jinyou Shen (Journal of Hazardous Materials, 2025)

Experimental study on longitudinal shear resistance in composite frame beams under lateral loads - Mu-Xuan Tao; Tian-Shu Liu; Ji-Zhi Zhao (Engineering Structures, 2025)

Phosphorus speciation, controlling factors, and ecological risk assessment in lagoon sediments: a case study of the Shamei Lagoon, Qionghai, Hainan - Kun Yuan; Xuan Mu; Guangning Xiao; Kexin Li; Wantong Zhou; Rui Wang; Shisheng Wang (Frontiers in Marine Science, 2025)
The Shamei Lagoon in Qionghai, Hainan, is an ecologically significant coastal wetland system that has recently faced increasing ecological risks due to phosphorus (P) pollution. In this study, 22 sediment samples were systematically collected from the main lagoon body, river inlets, and the transitional zone to the open sea. A comprehensive approach incorporating standardized phosphorus fractionation, spatial interpolation, redundancy analysis, and ecological risk assessment was used to investigate P speciation, spatial distribution patterns, controlling factors, and ecological risks. The results showed that: (1) Total phosphorus (TP) concentrations ranged from 261.87 to 875.74 mg/kg, with a mean of 415.72 mg/kg, comparable to typical lagoons in China. Inorganic phosphorus (IP) dominated the P fractions (mean: 317.70 mg/kg), with Fe/Al-bound phosphorus (Fe/Al-P, mean: 183.52 mg/kg) markedly exceeding Ca-bound phosphorus (Ca-P, mean: 105.88 mg/kg). Organic phosphorus (OP) had the lowest contribution (mean: 98.02 mg/kg). (2) The primary sources of P pollution were agricultural runoff and aquaculture waste, industrial discharges and vessel leakage, and regional calcareous deposition. High TP and OP concentrations were concentrated in the southwest river inlet zone, directly linked to fertilizer runoff and tourism-related wastewater. IP levels were elevated in the southern region, driven by hydrodynamic processes. Fe/Al-P was enriched in the central lagoon, likely associated with oil degradation from vessels. Secondary peaks of Ca-P occurred in the southwest aquaculture zone and the northeastern mangrove area, attributed to feed residues and shell debris, respectively. (3) Cation exchange capacity (CEC) was identified as the primary controlling factor for spatial variation in P speciation (explained variance: 46.0%, p < 0.01), followed by organic matter (OM), while pH exhibited a marked negative regulatory effect. (4) At 45.5% of sampling sites, TP levels exceeded the ecological safety threshold (600 mg/kg), and 18 sites, mainly located near the river mouth and central lagoon, were classified as heavily polluted, posing a threat to aquatic ecological security. These findings indicate that sediment P pollution in the Shamei Lagoon is driven by multiple anthropogenic activities. Mitigation strategies should prioritize control of agricultural non-point sources, aquaculture residues, and vessel oil pollution, along with sediment remediation focused on enhancing CEC.

Chromium deposition enhances the tolerance of Chlorella vulgaris to microplastics - Yuanyuan Wei; Xuan Hou; Xiangang Hu; Li Mu (Journal of Hazardous Materials, 2025)

Microencapsulation of Acer truncatum seed oil using chickpea protein isolate–low/high-methoxy citrus pectin complex coacervates: Preparation, stability analysis, and application in milk - Mo Chen; Bo Zhang; Min Wang; Jin-yue Sun; Mu-xuan Wang; Meng-qi Zhang; Ying-ying Chen; Qi-dong Ren; Shu-tao Sun; Mohamed A. Farag; Xu Guo; Chao Liu (Food Hydrocolloids, 2025)

Impact of marine chlorine emissions on secondary organic aerosols in North China Plain - Zhaoqi Gao; Lin Li; Zhou Liu; Jiangshan Mu; Zhuyi Wang; Bin Luo; Jingzhu Zhang; Shuting Tang; Hongliang Zhang; Jianlin Hu; Xuan Wang; Xuehua Zhou; et al. (Environmental Pollution, 2025)

Impact of convergence rate and slab dip angle on island-arc magma generation - Yongliang Bai; Wenzhao Zhang; Shiguo Wu; Dongdong Dong; Xuan Mu; Jiahao Tian; Yuanpeng Liu (Journal of Oceanology and Limnology, 2025)

BRCA-CN: a blockchain-based framework to support public variant databases sharing in multi-center community for diagnostic reference and China regulatory science - Shoufang Qu; Rongzhi Liu; Shisen Li; Chuanfeng Huang; Yingqian Zhang; Xuan Gao; Pingping Dai; Chao Xu; Rutao Yang; Xuchao Li; Guojun Ouyang; Kang Shao; et al. (Human Genetics, 2025)

Unrecognized role of photosynthetic bacteria in aquaculture water purification: Producing singlet oxygen to degrade residual pharmaceuticals - Mu-Cen Yao; Qi Huang; Hong-Xuan Xie; Xin Zhang; Guo-Ping Sheng (Water Research, 2025)

A new control strategy of sulfate-reducing microorganisms and corrosion rate from a high-temperature oil reservoir by nitrate/nitrite coupling with nitrate-reducing bacteria - Lei Zhou; Jie Gao; Yu-Xuan Li; Jun Wu; Biao Wang; Yi-Fan Liu; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

Preparation and characterization of microcapsules for tuna oil by maillard reaction products of whey protein isolate and Arabic gum via complex coacervation - Kun-Long Wang; Bo-Kang Yu; Hong-Fu Zhao; Ye-Xuan Liu; Chun-Ying Wu; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Constructing sodium L-aspartate assisted N-doped carbon encapsulated hollow CoP spheres with enhanced electrochemical kinetics and its derived macroporous N-doped carbon foam for high-energy density hybrid supercapacitors - Xiaolin Liu; Tian Tian; Aifeng Liu; Zengcai Guo; Jingbo Mu; Xiaoliang Zhang; Xuan Yue; Xiaoyan Liu; Fei Gao; Hongwei Che (Chemical Engineering Journal, 2025)

Molecular networking and Paterno-Büchi reaction guided glycerides characterization and antioxidant activity assessment of Ganoderma lucidum spore oil - Qing-Xuan Ren; Rui Wang; Qin-Ru Mu; Ling Chen; Min Chen; Li-Jiang Wang; Ping Li; Hua Yang; Wen Gao (Food Chemistry, 2025)

Deciphering the key role of biofilm and mechanisms in high-strength nitrogen removal within the anammox coupled partial S0-driven autotrophic denitrification system - Shuyan Yin; Yi-Xuan Wang; Cheng Hou; Jing Wang; Jing Xu; Xinbai Jiang; Dan Chen; Yang Mu; Jinyou Shen (Bioresource Technology, 2025)

An overview of the chirality of diet-related fatty acids, glycerolipids, and glycerophospholipids - Shu-tao Sun; Yan-jie Jiang; Xu Guo; Meng-qi Zhang; Qi-dong Ren; Jesus Simal-Gandara; Mu-xuan Wang; Xiao-jia Xue; Ning-yang Li; Chao Liu (Trends in Food Science & Technology, 2025)

Heatwaves increase the polystyrene nanoplastic-induced toxicity to marine diatoms through interfacial interaction regulation - Xuan Hou; Xiangang Hu; Li Mu; Yuanyuan Wei (Journal of Hazardous Materials, 2025)

Effect of microplastics concentration and size on pollutants removal and antibiotic resistance genes (ARGs) generation in constructed wetlands: A metagenomics insight - Lin Liang; Weiliang Pan; Merui Mu; Lin Zhang; Xiangyu Yang; Ruina Zhang; Lianfeng Du; Xuan Guo (Journal of Hazardous Materials, 2025)

Stochastic processes driving cyanobacterial temporal succession in response to typhoons in a coastal reservoir - Yajun Wang; Tianzheng Cao; Qingqing Liu; Boyu Xuan; Zhengyuan Mu; Jian Zhao (Water Research, 2024)

Boosting bioelectricity generation in bioelectrochemical systems with nitrogen-doped three-dimensional graphene aerogel anode - Yi-Xuan Wang; Xiao-Li Liu; Wen-Qiang Li; Yi-Ran Wang; Ke-Wan Li; Zhi-Cheng Pan; Yang Mu (Water Research, 2024)

Spatial variations of the relationships between bacterial diversity and forest ecosystem multifunctionality in the Qinling Mountains, China - Manya Luo; Xia Jia; Yonghua Zhao; Xuan Ye; Kun Ren; Qi Mu; Shuaizhi Kang; Huanyuan Wang; Juan Li (Applied Soil Ecology, 2024)

Boosting persulfate activation through efficient π → π* transition activated by Cu ion anchored porphyrin-based metal–organic framework - Wen-Qiang Li; Oleksandr Savateev; Yuan-Ming Li; Jian-Kang Zheng; Yi-Xuan Wang; Nannan Hou; Xiao-Cheng Liu; Rong-Rong Ding; Xiao-Guo Zhou; Yang Wang; Xian-Yang Shi; Yang Mu (Chemical Engineering Journal, 2024)

Material and microbial perspectives on understanding the role of biochar in mitigating ammonia inhibition during anaerobic digestion - Zhi-Jun Zhao; Xiao-Li Liu; Yi-Xuan Wang; Yan-Shan Wang; Jin-You Shen; Zhi-Cheng Pan; Yang Mu (Water Research, 2024)

Factors affect the oxygen production of Chlorella pyrenoidosa in a bacterial-algal symbiotic system: Light intensity, temperature, pH and static magnetic field - Shiyu Yin; Wenbiao Jin; Tingting Xi; Xu Zhou; Zhongqi He; Xuli Meng; Mu. Naushad; Guangming Jiang; Xuan Li (Process Safety and Environmental Protection, 2024)

Member separation and deformation recognition of spatial grid structures in-service - Mu-Nan Xu; Li-Min Sun; Yu-Fei Liu; Bao-Luo Li; Meng Zhou; Xuan Chen (Engineering Structures, 2024)

Development of an alternative low-cost culture medium for a new isolated high-production DHA strain using kitchen wastewater - Qing Wang; Wenbiao Jin; Yujia Qin; Xu Zhou; Wei Han; Shuhong Gao; Xuan Li; Mu. Naushad; Guangming Jiang; Huan Liu (Process Safety and Environmental Protection, 2024)

Brunonianines A-C, C20-diterpenoid alkaloids with cyano group from Delphinium brunonianum Royle - Qing Li; Zhi-Wei Wang; Mu-Xuan Wang; Hao-Lin Yu; Lei Chen; Zhuoer Cai; Yu Zhang; Min-Min Gu; Yuan-Ling Shao; Hong-Ping Han; Zhi-Xin Liao (Phytochemistry, 2024)

Dynamic responses of multi-story structural systems with separated gravity and lateral resisting systems under seismic action considering connection semi-rigidity effects - He Zhao; Xin-Yu Qian; Xiao-Gang Liu; Hong-Bing Chen; Mu-Xuan Tao (Engineering Structures, 2024)

Life-cycle analysis of biohydrogen production via dark-photo fermentation from wheat straw - Mingjie Jin; Xuan Wei; Xuefang Mu; Weixi Ren; Sihu Zhang; Canfang Tang; Wen Cao (Bioresource Technology, 2024)

Biogeography and diversity patterns of functional genes associated with C, N, P, S cycling processes across China classical sea sediments - Shuai Liu; Xin Huang; Hongyu Mu; Minggang Zheng; Shaoping Kuang; Hui Chen; Yan Xu; Dong Wang; Huan Liu; Xuan Li (Science of The Total Environment, 2024)

The gradient fabrication and optimization of metal-acid bifunctional catalysts for the hydrogenation of n-C16 to produce bio-jet fuel component - Junhao Sun; Yingying Yu; Chao Mu; Xuan Guo; Yujun Zhao; Shengping Wang; Xinbin Ma (Fuel, 2023)

The molecular basis of heat stress responses in plants - Yi Kan; Xiao-Rui Mu; Jin Gao; Hong-Xuan Lin; Youshun Lin (Molecular Plant, 2023)

Maximizing jet fuel production from n-hexadecane hydrocracking over Pt-supported Y catalysts: Importance of ideal hydrocracking characteristics - Yi Li; Chao Mu; Guangxin Chu; Yule Wang; Jing Xu; Xuan Guo; Yujun Zhao; Shengping Wang; Xinbin Ma (Fuel, 2023)

Proteomic analysis reveals mechanisms of mixed wastewater with different N/P ratios affecting the growth and biochemical characteristics of Chlorella pyrenoidosa - Xinrui Mao; Xu Zhou; Xiumin Fan; Wenbiao Jin; Jingjing Xi; Renjie Tu; Mu. Naushad; Xuan Li; Huan Liu; Qilin Wang (Bioresource Technology, 2023)

The dynamic amplification effect of a site with earth fissures: a case study in the Taiyuan Basin, China - Jiang Chang; Yahong Deng; Ge Cao; You Xuan; Nainan He; Xunchang Zhao; Huandong Mu (Journal of Seismology, 2023)

Short-chain fatty acids (SCFAs) as potential resuscitation factors that promote the isolation and culture of uncultured bacteria in marine sediments - Chun-Shui Sun; Liu-Yan Zhou; Qi-Yun Liang; Xiao-Man Wang; Yi-Xuan Lei; Zhen-Xing Xu; Feng-Qing Wang; Guan-Jun Chen; Zong-Jun Du; Da-Shuai Mu (Marine Life Science & Technology, 2023)
Many marine bacteria are difficult to culture because they are dormant, rare or found in low-abundances. Enrichment culturing has been widely tested as an important strategy to isolate rare or dormant microbes. However, many more mechanisms remain uncertain. Here, based on 16S rRNA gene high-throughput sequencing and metabolomics technology, it was found that the short-chain fatty acids (SCFAs) in metabolites were significantly correlated with uncultured bacterial groups during enrichment cultures. A pure culture analysis showed that the addition of SCFAs to media also resulted in high efficiency for the isolation of uncultured strains from marine sediments. As a result, 238 strains belonging to 10 phyla, 26 families and 82 species were successfully isolated. Some uncultured rare taxa within Chlorobi and Kiritimatiellaeota were successfully cultured . Amongst the newly isolated uncultured microbes, most genomes, e.g. bacteria, possess SCFA oxidative degradation genes, and these features might aid these microbes in better adapting to the culture media. A further resuscitation analysis of a viable but non-culturable (VBNC) Marinilabiliales strain verified that the addition of SCFAs could break the dormancy of Marinilabiliales in 5 days, and the growth curve test showed that the SCFAs could shorten the lag phase and increase the growth rate. Overall, this study provides new insights into SCFAs, which were first studied as resuscitation factors in uncultured marine bacteria. Thus, this study can help improve the utilisation and excavation of marine microbial resources, especially for the most-wanted or key players.

Impacts of site real-time adaptive control of water-sensitive urban designs on the stormwater trunk drainage system - Xuli Meng; Xuan Li; Allan Charteris; Zhenyao Wang; Mu. Naushad; Long D. Nghiem; Huan Liu; Qilin Wang (Journal of Water Process Engineering, 2023)

Microtremor-based analysis of the dynamic response characteristics of a site containing grouped earth fissures - Yahong Deng; You Xuan; Huandong Mu; Jiang Chang; Ge Cao; Nainan He; Xunchang Zhao; Longfei Sun (Earthquake Engineering and Engineering Vibration, 2023)

Concurrence of microplastics and heat waves reduces rice yields and disturbs the agroecosystem nitrogen cycle - Shuqing Guo; Li Mu; Shan Sun; Xuan Hou; Mingqi Yao; Xiangang Hu (Journal of Hazardous Materials, 2023)

Underlying mechanisms for natural organic matters mediated aerobic ciprofloxacin transformation by sulfide - Han-Qing Zhao; Peili Lu; Fei Chen; Hongcheng Bai; Chen-Xuan Li; Guan-Nan Zhou; Jing Wang; Lilan Zhang; Yang Mu (Journal of Environmental Chemical Engineering, 2023)

A seminal perspective on the role of chondroitin sulfate in biomineralization - Jia-xin Hao; Qian-qian Wan; Zhao Mu; Jun-ting Gu; Wei-wei Yu; Wen Qin; Yu-tao Li; Chen-yu Wang; Yu-xuan Ma; Kai Jiao; Franklin Tay; Lina Niu (Carbohydrate Polymers, 2023)

Internal force redistribution caused by cracking of concrete in composite frame structures under lateral load - Mu-Xuan Tao; Yu-Lun Wang; Ji-Zhi Zhao (Engineering Structures, 2023)

Warming and microplastic pollution shape the carbon and nitrogen cycles of algae - Xuan Hou; Li Mu; Xiangang Hu; Shuqing Guo (Journal of Hazardous Materials, 2023)

Experimental study on in-plane behavior of composite frame slabs and the influence of out-of-plane effect - Wen-Hao Pan; Mu-Xuan Tao; Chuan-Hao Zhao; Ran Ding; Li-Yan Xu (Engineering Structures, 2023)

Formation mechanisms and atmospheric implications of summertime nitrous acid (HONO) during clean, ozone pollution and double high-level PM2.5 and O3 pollution periods in Beijing - Huiying Xuan; Yaqi Zhao; Qingxin Ma; Tianzeng Chen; Jun Liu; Yonghong Wang; Chang Liu; Yafei Wang; Yongchun Liu; Yujing Mu; Hong He (Science of The Total Environment, 2023)

Comparisons of cirrus clouds and their linkages to meteorology at the SACOL and the SGP sites - Zixiang Dong; Jinming Ge; Ang Gao; Zeen Zhu; Jialin Yan; Qingyu Mu; Jing Su; Xuan Yang; Xiaoyu Hu (Atmospheric Research, 2023)

Two new alkaloids from Tibetan medicine of Hypecoum leptocarpum - Bo Sun; Israa Assani; Chun-Gu Wang; Mu-Xuan Wang; Ling-Fei Liu; Yan Li; Ge Yan; Yun-Ruo Yang; Zhi Chen; Zhi-Xin Liao (Natural Product Research, 2022)

Effects of tillage and cropping sequences on crop production and environmental benefits in the North China Plain - Wen-Xuan Liu; Wen-Sheng Liu; Mu-Yu Yang; Yu-Xin Wei; Zhe Chen; Ahmad Latif Virk; Rattan Lal; Xin Zhao; Hai-Lin Zhang (Environmental Science and Pollution Research, 2022)

Sestrin2 attenuates renal damage by regulating Hippo pathway in diabetic nephropathy - Yawei Bian; Chonglin Shi; Shan Song; Lin Mu; Ming Wu; Duojun Qiu; Jiajia Dong; Wei Zhang; Chen Yuan; Dongyun Wang; Zihui Zhou; Xuan Dong; et al. (Cell and Tissue Research, 2022)

Robiginitalea marina sp. nov., isolated from coastal sediment - Xiao-Qi Xuan; Run-Yuan Mao; Wen-Xing Yu; Jing An; Zong-Jun Du; Da-Shuai Mu (Archives of Microbiology, 2022)

Dynamic characteristics of fault-controlled earth fissure sites in Jingyang County, Weihe Basin, China - You Xuan; Yahong Deng; Jiang Chang; Huandong Mu; Ge Cao (Acta Geophysica, 2022)

Overexpression of Cpg15 Alleviates the Oxidative Stress in Neuronal Cells Via Regulating Redox Enzymes and Nrf2 Antioxidative Pathway - Yi Jiang; Jun-Jie Li; Ya-Wei Mu; Han-Yang Jiang; Zi-Xuan Wei; Zi-Yao Xiao; Jing-Jing Zhao; Xian-Hua Chen (Neurotoxicity Research, 2022)

Two new diterpenoids with their antiproliferative activities from the supercritical fluid extraction of Croton crassifolius root - Chao Liu; Rui-rui Zhang; Qing-lin Niu; Jing Zhang; Mu-xuan Wang; Na-na Meng; Qing Wang; Jin-yue Sun; Wen-liang Wang (Natural Product Research, 2021)

Mechanical and Failure Characteristics of Rock-coal-rock Combined Body under Different Strain Rates: A Numerical Study from Micro Perspective - Shu-ning Dong; Ang Li; Ya-dong Ji; Yu-xuan Yang; Qian Mu (Geotechnical and Geological Engineering, 2021)

Influence of slab spatial composite effect on dynamic behaviour of composite frame structures under earthquake excitation - Xiao-Qiang Wang; Li-Yan Xu; Mu-Xuan Tao (Bulletin of Earthquake Engineering, 2019)

Roles of flotillins in tumors - Xu-xu Liu; Wei-dong Liu; Lei Wang; Bin Zhu; Xiao Shi; Zi-xuan Peng; He-cheng Zhu; Xing-dong Liu; Mei-zuo Zhong; Dan Xie; Mu-sheng Zeng; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2018)

Fiber beam–column element model considering reinforcement anchorage slip in the footing - Wen-Hao Pan; Mu-Xuan Tao; Jian-Guo Nie (Bulletin of Earthquake Engineering, 2017)

A correlation between acute kidney injury and myonecrosis after scheduled percutaneous coronary intervention - Min Zhang; Hao-yu Meng; Ying-ming Zhao; Zhi-wen Tao; Xiao-xuan Gong; Ze-mu Wang; Bo Chen; Zheng-xian Tao; Chun-jian Li; Tie-bing Zhu; Lian-sheng Wang; Zhi-jian Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Soil erosion changes over the past five decades in the red soil region of Southern China - Yin Liang; Decheng Li; Xixi Lu; Xuan Yang; Xianzhang Pan; Huan Mu; Deming Shi; Bin Zhang (Journal of Mountain Science, 2010)

Plants interactions between Suaeda salsa individuals are mediated by salinity stress - Hao Zhang; Jian-Na Li; Gen-Xuan Wang; Xin-Feng Dai; Mu-Qing Qiu; Ke-Feng Zheng (Acta Physiologiae Plantarum, 2007)

Effect of sensitivity to abscisic acid on scaling relationships for biomass production rates and body size in Arabidopsis thaliana - Hao Zhang; Gen-Xuan Wang; Zhu-Xia Shen; Xing-Zheng Zhao; Mu-Qing Qiu (Acta Physiologiae Plantarum, 2006)

Impact of elevated CO2 concentration under three soil water levels on growth of Cinnamomum camphora - Xing-zheng Zhao; Gen-xuan Wang; Zhu-xia Shen; Hao Zhang; Mu-qing Qiu (Journal of Zhejiang University-SCIENCE B, 2006)